2022
DOI: 10.1007/s11033-022-07200-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between the single nucleotide variants of the mitochondrial cytochrome B gene (MT-CYB) and the male infertility

Abstract: Background Idiopathic male infertility can be attributed to genetic predispositions that affect sperm performance and function. Genetic alterations in the mitochondrial DNA (mtDNA) have been linked to certain types of male infertility and abnormal sperm function. Mutations in the mitochondrial cytochrome B (MT-CYB) gene might lead to some deficiencies in mitochondrial function. Thus, in the current study, we aimed to investigate the effect of mutations in the MT-CYB gene on sperm motility and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…For instance, a recent study reported a significant correlation between polymorphisms of the MT-CYB gene and sub-fertility in men. Particularly, rs527236194, rs28357373 and rs41504845 variants were found significantly related to the sub-fertility group [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent study reported a significant correlation between polymorphisms of the MT-CYB gene and sub-fertility in men. Particularly, rs527236194, rs28357373 and rs41504845 variants were found significantly related to the sub-fertility group [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The isolated DNA was used for further selective purification and enrichment of mitochondrial ChrMT DNA using a REPLI-g Mitochondrial DNA Kit (Qiagen, Germantown, MD), based on the recommendation of the manufacturer. Briefly, the isolated DNA sample, from either the cells or the plasma pellet, was added to the REPLI-g reaction buffer mixed with REPLI-g human mitochondrial primers, preincubated at 75°C for 5 min, followed by adding DNA polymerase, incubating at 33°C for 8 hours, and then inactivation of the enzyme at 65°C for 3 min [ 19 , 20 ]. The ChrMT DNA was isolated from the cells (including WBCs/platelets) and the plasma ( Figure 2 ) and stored at −80°C before the sequencing analysis.…”
Section: Case Presentationmentioning
confidence: 99%
“…It is physically associated with the inner mitochondrial membrane, where free oxygen radicals are generated [50]. Recently, an association was discovered between the single nucleotide variants of the mitochondria cytochrome B gene (MT-CYB) and male infertility [52].…”
Section: Mitochondrial Dna Mutationmentioning
confidence: 99%